Aqua oxyhydroxycarbonate second phases at the surface of Ba/Sr‐based proton conducting perovskites: a source of confusion in the understanding of proton conduction. (26th September 2012) - Colomban, Ph.; Tran, C.; Zaafrani, O.; Slodczyk, A.
Abstract : Ba/Sr‐based zirconates and cerates appear as potential proton conducting electrolytes for water electrolysers, hydrogen fuel cells and CO2 /syngas converters. Such application requires long lifetime of each components: a good chemical and thermal stability of the device core and a low reactivity of the electrolyte membrane. It has been recently revealed that the complex infrared (IR) and Raman signatures observed for series of zirconates, cerates and/or titanates, assigned by some authors to the bulk protonic species actually arose from the surface species in the form of second undesirable phases: the high dense proton conducting ceramics being free from such signatures. In order to contribute to a better characterization of the phases that can be formed on the surface of proton conducting ceramics, we analysed the IR and Raman spectra of Ba/SrO, Ba/Sr(OH)2, Ba/SrCO3 in their dry and hydrated/deuterated forms in combination with thermogravimetric analysis. The results allowed us to confirm the above claim and to re‐assign the vibrational spectra of perovskite materials wrongly attributed to the bulk protonic species. Since these second phases exhibit a high proton conductivity, their presence is very detrimental in the determination of intrinsic electrolyte bulk properties and interpretation of the conduction mechanisms. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Ba/Sr‐based zirconates and cerates appear as potential proton conducting electrolytes for water electrolysers, hydrogen fuel cells and CO2 /syngas converters. Their complex vibrational signatures assigned by some authors to the bulk protonic species actually arose from the surface species ‐ a mixture of Ba/SrO, Ba/Sr(OH)2 and Ba/SrCO3 . Since these second phases exhibit high proton conductivity, their presence is very detrimental in the determination of intrinsic electrolyte bulk properties and interpretation of the conduction mechanisms.